Establishing Best Practices and Guidance in Population Modeling: An Experience With an Internal Population Pharmacokinetic Analysis Guidance. (3rd July 2013) - Byon, W; Smith, MK; Chan, P; Tortorici, MA; Riley, S; Dai, H; Dong, J; Ruiz‐Garcia, A; Sweeney, K; Cronenberger, C
Abstract : This tutorial describes the development of a population pharmacokinetic (Pop PK) analysis guidance within Pfizer, which strives for improved consistency and efficiency, and a more systematic approach to model building. General recommendations from the Pfizer internal guidance and a suggested workflow for Pop PK model building are discussed. A description is also provided for mechanisms by which conflicting opinions were captured and resolved across the organization to arrive at the final guidance. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e51; doi:10.1038/psp.2013.26 ; advance online publication 3 July 2013